Narrative in Form: A topological study of meaning in transmedial narratives. Issue 3 (11th November 2016) - Giannoukakis, Marinos
Abstract : This article is an attempt to demonstrate the relation between appreciation of morphology and structure in form on the one hand, with higher symbolic structures – crucial for meaning formation routines – on the other, and to evaluate their significance in transmedial narratives, primarily in the case of media-based artworks. The use of catastrophe theoretical models to classify forms, their structure and dynamics is proposed, and the question of how these models can give us insight into the meaning that is carried through transmedial narratives (referential or abstract) is examined. Finally, the value of these insights for the composition and practice-based analysis of multimedia art forms is demonstrated.